Measurement of the branching fraction, polarization, and CP asymmetries in B-0 ->rho(0)rho(0) decay, and implications for the CKM angle alpha - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
We study B0→ρ0ρ0 decays in a sample of 465×106 Υ(4S)→BB̄ events collected with the BABAR detector at the PEP-II asymmetric-energy e+e- collider located at the Stanford Linear Accelerator Center (SLAC). We measure the branching fraction B=(0.92±0.32±0. 14)×10-6 and longitudinal polarization fraction fL=0.75-0.14+0. 11±0.05, where the first uncertainty is statistical and the second is systematic. The evidence for the B0→ρ0ρ0 signal has a significance of 3.1 standard deviations, including systematic uncertainties. We investigate the proper-time dependence of the longitudinal component in the decay and measure the CP-violating coefficients SL00=(0.3±0.7±0.2) and CL00=(0.2±0.8±0.3). We study the implication of these results for the unitarity triangle angle α. © 2008 The American Physical Society.